CLCA1 mediates the regulatory effect of IL-13 on pediatric asthma - Xu, Yanan; Cao, Lili; Chen, Jiong; Jiang, Danyan; Ruan, Peisen; Ye, Qinsong (Frontiers in Pediatrics, 2022)
Objective: CLCA1 is a secreted protein with protease activity, and its expression is associated with inflammatory airway diseases. This study aimed to investigate the role of CLCA1 and IL-13 in pediatric asthma. Methods: In asthmatic and healthy children, the correlation between CLCA1 expression and blood IL-4, and IL-13 levels were investigated by serological analyses such as RT-qPCR and ELISA. The effects on the activity and apoptosis of bronchial epithelial cells following IL-13 stimulation were explored in vitro by the CCK-8 assay and flow cytometry, respectively. CLCA1 siRNA was used to knock down the expression level of bronchial epithelial cells and the effect of IL-13 stimulation on these cells was assessed by the CCK-8 assay and flow cytometry. Results: CLCA1, IL-4, and IL-13 were highly expressed in the serum of children with asthma. CLCA1 expression was highly correlated to serum IL-13. IL-13 stimulation reduced the activity of bronchial epithelial cells in vitro and promoted apoptosis. Lastly, knockdown of CLCA1 rescued the IL-13-induced decrease in activity and apoptosis. Conclusion: CLCA1 is highly expressed in children with asthma and mediates the contributory effect of IL-13 on the occurrence and development of pediatric asthma.